Spatial variation in stable isotopes and fatty acid trophic markers in albacore tuna (Thunnus alalunga) from the western Indian Ocean. (July 2020) - Dhurmeea, Zahirah; Pethybridge, Heidi; Langlais, Clothilde; Somes, Christopher J.; Nikolic, Natacha; Bourjea, Jérôme; Appadoo, Chandani; Bodin, Nathalie
Abstract: Albacore tuna ( Thunnus alalunga ) is a highly economically important species in the western Indian Ocean. However, knowledge of its ecological and nutritional characteristics, essential for proper management of the species, is lacking in the region. The trophodynamics of the Indian Ocean albacore was thus examined using known fatty acid trophic markers (FATMs) of primary producers, nutritional condition indices (NCIs) (omega-3/omega-6 ratio and total fatty acid content (TFA)), and baseline and lipid corrected stable isotope of carbon (δ 13 Ccorr ) and nitrogen (δ 15 Ncorr ), measured in the muscle tissue. We applied generalized additive mixed models to understand the spatiotemporal patterns and drivers of these tracers, taking into consideration several intrinsic and extrinsic variables: fish size, fishing position, month, chlorophyll- a and sea surface temperature (SST). Both chlorophyll- a and SST were significant as single explanatory variables for all tracers with SST being the best predictor for docosahexaenoic acid/eicosapentaenoic acid ratio, the omega-6 protists FATM, omega-3/omega-6 ratio, δ 13 Ccorr and δ 15 Ncorr . TFA was best predicted by fish size only. Higher primary productivity, as inferred by high δ 13 Ccorr values and diatom contribution, nutritional condition and trophic position, as inferred by high δ 15 Ncorr values, were observed in albacore from the temperate southern waters than in the northern tropical regions. Relationships between environmental variables and corrected stable isotopes, FATMs confirm that ocean warming and changes in primary productivity will impact nutrient flow and energy transfer in the marine food web which may have negative nutritional outcomes for albacore. This knowledge is particularly crucial in areas where oceanographic conditions and seawater temperatures are changing at a fast rate and should also be taken into consideration by fisheries managers. Highlights: A multi-tracer approach was taken to examine the trophodynamics of albacore tuna. Albacore inhabiting temperate southern waters feed on a diatom-based food web. Albacore trophic position was lowest in the northern tropical waters. Ontogenetic shifts in stable carbon and nitrogen isotopes were observed. High seawater temperature lowers the nutritional condition of albacore.